REAKTOR INNOVATIVE MOLTEN SALT (IMSR) DENGAN SISTEM KESELAMATAN PASIF MENYELURUH - Harto, Andang Widi (Jurnal Teknologi Reaktor Nuklir Tri Dasa Mega, 2015)
The next Nuclear Reactor Technology developments are directed to the increasing of the aspects of safety, fuel utility, radioactive waste reduction, proliferation retention and economy. Innovative Molten Salt Reactor (IMSR) is a nuclear reactor design that uses fluoride molten salt (7LiF-ThF4-UF4-MaFx). IMSR is designed as a thermal breeder reactor, i.e. to produce U-233 from Th-232. This is the answer of natural nuclear fuel sustainability and radioactive waste problems. In term of safety aspect, IMSR design has inherent safe characteristics, i.e. negative power feedback coefficient, and passive safety features. The passive safety features are passive shutdown systems, passive post shutdown cooling system and passive radioactive waste cooling system. The potentially accidents in IMSR, i.e. loss of fuel flow accident, loss of coolant flow accident, loss of heat sink accident and loss of reactor system integrity, can be handled totally passively until the safe shutdown condition is achieved.